2022
DOI: 10.1080/14756366.2022.2081847
|View full text |Cite
|
Sign up to set email alerts
|

From the Wuhan-Hu-1 strain to the XD and XE variants: is targeting the SARS-CoV-2 spike protein still a pharmaceutically relevant option against COVID-19?

Abstract: Since the outbreak of the COVID-19 pandemic in December 2019, the SARS-CoV-2 genome has undergone several mutations. The emergence of such variants has resulted in multiple pandemic waves, contributing to sustaining to date the number of infections, hospitalisations, and deaths despite the swift development of vaccines, since most of these mutations are concentrated on the Spike protein, a viral surface glycoprotein that is the main target for most vaccines. A milestone in the fight against the COVID-19 pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…The Alpha variant (B.1.1.7) was the first labeled variant of concern (VOC) with 29% increased transmissibility and signs of immune escape [ 33 ]. Followed the Delta variant (B.1.617.2), which rapidly became the dominant strain in the world, thanks to 97% increased transmissibility and significant immune escape effect [ 34 , 35 , 36 ]. In Bulgaria, alpha VOC was detected in June 2020 and dominated during the period of the second and the third wave until 2021, when Delta was detected for the first time [ 37 ] and was the leading cause of morbidity and mortality during the fourth and fifth wave.…”
Section: Discussionmentioning
confidence: 99%
“…The Alpha variant (B.1.1.7) was the first labeled variant of concern (VOC) with 29% increased transmissibility and signs of immune escape [ 33 ]. Followed the Delta variant (B.1.617.2), which rapidly became the dominant strain in the world, thanks to 97% increased transmissibility and significant immune escape effect [ 34 , 35 , 36 ]. In Bulgaria, alpha VOC was detected in June 2020 and dominated during the period of the second and the third wave until 2021, when Delta was detected for the first time [ 37 ] and was the leading cause of morbidity and mortality during the fourth and fifth wave.…”
Section: Discussionmentioning
confidence: 99%
“…In recent a prospective, open-label, randomized controlled trial (ChiCTR2 200060292), Xu et al [96] demonstrated that treatment with Reyanning (RYN) mixture accelerated virus clearance and promoted disease recovery in patients with asymptomatic and mild Omicron infections, and disease progression or serious adverse events were not observed. Pavan et al [97] analysed the structural features of the S protein and Main Protease (Mpro) of XE, XD, and XF, and proposed the development of pan-coronaviral drugs that could prevent future coronavirus-associated pandemics. Given that some antiviral drugs can lose activity against circulating BA.5, COVID-19 convalescent plasma therapy will need to be revisited as a reliable therapeutic strategy in specific patient populations [98].…”
Section: Current Therapeutics Against Covid-19mentioning
confidence: 99%
“…Middle East Respiratory Syndrome (MERS) CoV and SARS-CoV-2 are exceptionally dangerous viruses that have been observed to spread from bats to people via intermediate hosts such as palm civets and dromedary camels (Guan et al 2003 ; Azhar et al 2014 ). Owing to the first reported sequence of SARS-CoV-2 from Wuhan, the reference variant has been named Wuhan-Hu-1 (Pavan et al 2022 ). The same nomenclature has been used in the present study.…”
Section: Introductionmentioning
confidence: 99%